Medicines for influencing the posttranslational modifications of histones – a tutorial review - Bege, Miklós; Borbás, Anikó (De Remediis, 2024)
Epigenetic therapy is a relatively novel, but undoubtedly a promising area of pharmacology. Most epigenetic drugs act by affecting enzymes and play a role in post-translational modifications of histones. The molecular targets of these medicines include histone methyltransferases, histone demethylases, isocitrate dehydrogenases, histone acetyltransferases and histone deacetylases. Since histone modifications are important regulatory signals, abnormalities in this process often lead to tumorigenesis, therefore these medicines constitute an important class of antitumor therapy. In this tutorial review, we would like to briefly overview the medicines that affect histone modifications, focusing on the currently approved ones, and briefly mention other interesting examples.